Conformation of acetate derivatives of sugars and other cyclic alcohols. Crystal structures, NMR studies, and molecular mechanics calculations of acetates. When is the exocyclic CO bond eclipsed?. - Nasser, Rima (2005)
A study of published crystal structures (of O-acetylated sugars for the most part) suggests that the exocyclic C−O bond in acetate esters of cyclic alcohols intrinsically prefers a staggered conformation, although the eclipsed conformation is only slightly less stable. When the acetate is flanked by two equatorial substituents the preferred conformation is close to eclipsed. Over 1500 C−OAc bonds have been analyzed. Diagnostic NMR criteria for torsion angles and MM3 calculations are reported and confirm these conclusions